Requeijão: tipos e propriedades - Pereira, Ana Cláudia Conhe (Universidade Federal de São Carlos, 2026)
Requeijão is a traditional Brazilian processed cheese with significant economic and technological importance due to its widespread consumption and broad range of culinary applications. Its manufacture involves the fusion of curd obtained by acid or enzymatic coagulation, combined with ingredients that determine the product's texture, spreadability, stability, and sensory acceptance. This study aimed to compile and discuss information regarding the different types of requeijão, addressing aspects related to its classification, formulation, processing, rheological properties, quality control, microbiological and physicochemical analyses, as well as the current national and international market. A literature review was conducted based on scientific articles, books, technical documents, and official regulations, emphasizing recent publications and recognized sources in the field of Food Science and Technology. The review demonstrated that formulation composition, fat content, pH, emulsifying salts, processing conditions, and the fusion step directly influence the structural, rheological, and sensory properties of requeijão. Furthermore, the growing demand for reduced-fat, lactose-free, and innovative products has driven the development of new technologies and ingredients for this dairy product. It is concluded that understanding the factors involved in the production and technological properties of requeijão is essential for developing safe, high-quality, and technologically stable products, contributing to innovation and competitiveness in the dairy industry.
Brazilian requeijão: types and properties
Keywords: Requeijão; Queijo processado; Derivados lácteos; Reologia; Processamento; Controle de qualidade; Processed cheese; Dairy products; Rheology; Processing; Quality control; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS; 12. Consumo e Produção Responsáveis; 9. Indústria, Inovação e Infraestrutura